2020
DOI: 10.1001/jamanetworkopen.2020.26874
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic and Phenotypic Assessments With Onset of Disordered Eating Behaviors and Comorbid Mental Health Problems Among Adolescents

Abstract: Key Points Question Do associations exist between disordered eating behaviors and other mental health disorders in adolescence, and if so, to what extent are those associations genetically predisposed? Findings Longitudinal assessments in this cohort study of a population-based sample of 1623 adolescents indicated that body mass index (BMI), neuroticism, impulse control, and addiction-related behaviors at 14 years of age were differentially associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
20
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 63 publications
(103 reference statements)
5
20
1
2
Order By: Relevance
“…Furthermore any given context information is added. The stylistic and chronological developments of the portraits have been studied on the basis of art-historical criteria [ 1 , 2 , 92 ] and the inscriptions which often accompany the portraits, whereof 4.2% give exact years of death, as well as in-situ portraits [ 93 , 94 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore any given context information is added. The stylistic and chronological developments of the portraits have been studied on the basis of art-historical criteria [ 1 , 2 , 92 ] and the inscriptions which often accompany the portraits, whereof 4.2% give exact years of death, as well as in-situ portraits [ 93 , 94 ].…”
Section: Methodsmentioning
confidence: 99%
“…These parameters are those well-established and widely used within classical archaeology and art historical approaches [i.e. 1 , 62 , 92 , 95 , 96 ]. Most of the stelai that can be associated with a known funerary monument come from underground tombs, for example, 1) stele with standing male and female [ 71 : p. 81, cat.…”
Section: Methodsmentioning
confidence: 99%
“…PGSs can be used to examine whether two traits are genetically related by associating the PGSs calculated for one trait with another trait. Our group (Abdulkadir et al, 2020) and others (Nagata et al, 2019; Robinson et al, 2020; Solmi, Mascarell, Zammit, Kirkbride, & Lewis, 2019) have successfully applied this method and reported that a BMI PGS and a schizophrenia PGS are associated with eating disorder symptoms (e.g., binge eating, fasting for weight loss, and body dissatisfaction) in the general population. However, a broader evaluation of PGSs indexing psychiatric and anthropometric/metabolic traits is warranted, as a GWAS on anorexia nervosa (AN) reported several significant genetic correlations with psychiatric, metabolic, and anthropometric traits (Duncan et al, 2017; Hübel et al, 2019; Watson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Binge eating at 14 years was associated with future purging at 16 or 19 years. [9] In China, negative emotions are still associated with binge eating. Family relationships, stress, and social standards that bring negative emotions are all factors that influence binge eating among teenagers.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 1.Time-Varying Associations and Outcomes of Disordered Eating Behaviors (DEBs) From 14 to 19 Years[9] …”
mentioning
confidence: 99%